2014
DOI: 10.2322/tastj.12.pe_11
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of Acoustic Waves from a Subscale Rocket Motor

Abstract: For improvement of prediction of acoustics waves from a rocket plume, validation studies of numerical simulation are performed using experimental data of acoustics waves from subscale rocket motors, and prediction accuracy of numerical simulation is discussed. Experimental data of flow and acoustics fields of a solid motor and a H2-AIR liquid motor are used as the reference. The computational results of the far-field OASPL agree with experimental data within the error of approximately 5dB. The result shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Toward the quantitative prediction, we devoted higher resolution LES for the acoustic waves from the rocket plume and showed that the prediction accuracy for the acoustic waves from the subscaled liquid rocket motor is approximately 5 dB. 3) However, the accuracy was still insufficient, because the accuracy of the experiments is approximately 2 dB. An important difference between the flow conditions of actual rocket motors and our previous computation is the inflow condition.…”
Section: Introductionmentioning
confidence: 93%
“…Toward the quantitative prediction, we devoted higher resolution LES for the acoustic waves from the rocket plume and showed that the prediction accuracy for the acoustic waves from the subscaled liquid rocket motor is approximately 5 dB. 3) However, the accuracy was still insufficient, because the accuracy of the experiments is approximately 2 dB. An important difference between the flow conditions of actual rocket motors and our previous computation is the inflow condition.…”
Section: Introductionmentioning
confidence: 93%
“…We have been conducting series of analyses on the acoustic waves from rocket plumes, [1][2][3] in which the mixing is a key phenomenon. In the case of rocket plume, we would like to quantify the effects of multicomponent gas compared with the single gas phenomena, by using numerical simulation.…”
Section: Introductionmentioning
confidence: 99%